2018
DOI: 10.1371/journal.pone.0202893
|View full text |Cite
|
Sign up to set email alerts
|

Genomics-guided discovery and structure identification of cyclic lipopeptides from the Bacillus siamensis JFL15

Abstract: In this research, a strain with broad-spectrum antimicrobial activities was isolated from the gastrointestinal tract of hairtail (Trichiurus haumela) and identified as Bacillus siamensis JFL15 through morphological, 16S rRNA, and average nucleotide identity analyses. The genome of B. siamensis JFL15 was sequenced, and three gene clusters involved in the biosynthesis of surfactin (srf), bacillibactin (dhb), and fengycin (fen) were predicted through antiSMASH analysis. The combined genomics-metabolics profiling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 40 publications
5
29
0
Order By: Relevance
“…In this study, the BCF of B. velezensis CE 100 displayed significant antifungal activities against the pathogen, C. gloeosporioides, which causes anthracnose disease in plants. Results of in vitro tests suggested the involvement of secondary metabolites, consistent with findings from several previous studies stating the promiscuous action of the secondary metabolites against fungal pathogens [14][15][16][42][43][44][45]. In this study, we identified a cyclic tetrapeptide compound from B. velezensis CE 100 culture filtrate based on one-and two-dimensional NMR spectral analysis.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, the BCF of B. velezensis CE 100 displayed significant antifungal activities against the pathogen, C. gloeosporioides, which causes anthracnose disease in plants. Results of in vitro tests suggested the involvement of secondary metabolites, consistent with findings from several previous studies stating the promiscuous action of the secondary metabolites against fungal pathogens [14][15][16][42][43][44][45]. In this study, we identified a cyclic tetrapeptide compound from B. velezensis CE 100 culture filtrate based on one-and two-dimensional NMR spectral analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Bacillus species demonstrating wide array of bioactive metabolites have been recognized as effective candidates to control several phytopathogens [ 14 , 15 , 16 , 42 , 43 , 44 , 45 ]. In this study, the BCF of B. velezensis CE 100 displayed significant antifungal activities against the pathogen, C. gloeosporioides, which causes anthracnose disease in plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar study conducted by Pan et al (2019) reported B. siamensis to produce sets of bacillibactins, fengycins, bacillomycins, and surfactins through the mining of genome and metabolic profiling. The PCR study demonstrated the existence of genes (i.e., surfactin synthetase D and bacillomycin synthetase D) involved in cyclic lipopeptide biosynthesis against multidrug-resistant aquatic bacterial pathogens (Xu et al, 2018). This concludes that so far, no endophytic strain of B. siamensis with antifungal potential has been reported to produce surfactin and Bacillomycin D. Complete isolation and identification of these lipopeptides from B. siamensis KCTC 13613(T) isolated from the varieties of tomato plants is first to be reported.…”
Section: Discussionmentioning
confidence: 99%